Penggunaan Media Sosial dan Perubahan Perilaku Sosial Remaja - Baiq Cintya Riexma Salsabila Al Hidayah; Siti Nurul Yaqinah; Ulya Hilalatul Hasbi (Jurnal Humanitas: Katalisator Perubahan dan Inovator Pendidikan, 2025)
Social media has become a phenomenon that affecting various aspects of people's lives, especially among teenagers. This article aims to analyse how social media life is perceived in today's social reality, especially in relation to the phenomenon of social media addiction. in looking at current social reality, especially related to the phenomenon of social media addiction in daily life. Social media addiction phenomenon in everyday life. The research uses the study method (library research) by collecting and analysing various sources such as books, scientific journals, articles, etc. Sources such as books, scientific journals, research articles, and other written documentation related to the topic of related to the topic of adolescent social change and social media. The results show that the use of social media and social change in society, especially teenagers, is very influential. Social change in society, especially teenagers, is very influential on the way they interact and share information in the era of digital technology. Interact and share information in the era of digital technology. Teenagers' lives and social interactions are influenced by social media, as seen from the social changes that occur such as the transformation of communication patterns, communication social changes that occur such as the transformation of communication patterns, evolution of interactions, dynamics of fashion, changes in habits, mindsets, and increased consumerism. Consumerism. Social interaction in the real world has decreased because teenagers communicate more through social media, which can result in a more closed society. a more closed society. In conclusion, social media has changed various social and cultural structures of society with significant impacts, both positive and negative, in the lives of adolescents as well as the resulting social changes.